The attitudes of children of overseas Filipino Workers of Miagao Iloilo toward working and living abroad. - Moreno, Glitter Hechanova
The study is conducted to elicit, describe and analyze the attitudes of the children of the OFWs of Miag-ao Iloilo toward working and living abroad. The study further seeks the factors that affect the attitudes of the respondents and statistically measure the differences in such attitudes by using the six characteristics of the respondents that were identified ; sex, age , civil status, educational attainment, birth order and age when parent first left., Both random and purposive samplings were administered in choosing the respondents and locale of the study. A Scale on the Attitude of Children of OFWs of Miagao Iloilo Toward Working and Living Abroad is used in the study. This consists of the different situations that will establish the positive, negative or neutral attitudes of OFWs children toward working and migrating abroad. The respondents were made to answe, using a 5-point rating scale with (1-strongly disagree, 2-disagree, 3-neutral, 4-agree, 5-strongly agree). Mode was used in obtaining the average , and Mann-whitney and Kruskal-Wallis tests were utilized to see if the opinions of the participants differ towards working and living abroad. There were 0 participants for the study. The research, revealed that 40 percent of the respondents have a positive attitude toward working and living abroad, 5 percent of them are negative about it, and more than half (55 percent) are neutral.